1,25-Vitamin D-mediated hypercalcaemia in the setting of immune therapy-related sarcoid-like reaction - R K Dharmaputra; N Sheriff; S Ravichandran (Endocrinology, Diabetes & Metabolism Case Reports)
We presented a case of a 72-year-old male with severe hypercalcaemia of 3.84 mmol/L following the second cycle of immunotherapy with ipilimumab and nivolumab in the setting of metastatic melanoma with known bone metastases. Further investigations demonstrated hilar lymphadenopathy, which was not present in previous imaging, and subsequent hypercalcaemia work-up demonstrated a significantly elevated serum calcitriol level as high as 429 pmol/L. A diagnosis of drug-induced sarcoid-like reactions or DISRs was made on the basis of hypercalcaemia and hilar lymphadenopathy following immunotherapy. Hypercalcaemia was effectively treated with intravenous fluids and medical therapy including a short course of subcutaneous calcitonin, a total of 120 mg of denosumab and oral prednisolone.